THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE, ENVIRONMENTAL COSTS, INSTITUTIONAL OWNERSHIP AND MANAGERIAL OWNERSHIP ON FINANCIAL PERFORMANCE - Shah, Teuku Faldian; Puspasari, Oktaviani Rita; Hamzah, Amir (Journal Socio Humanities Review, 2023)
This study aims to determine the effect of environmental performance, environmental costs, institutional ownership, and managerial ownership on financial performance. The research methods used in this study are descriptive and verification methods. The population in this study is Mining Sector Companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. Data samples were obtained using purposive sampling methods as many as 45 companies. The type of data used in this study is secondary data using financial statement data. The analysis technique used is panel data regression. Data processing using Eviews 9.0. The results showed that environmental performance, environmental costs, institutional ownership and managerial ownership together have a significant effect on financial performance. The partial test results show that dividend policy has a positive effect on company value, environmental performance has a positive effect on financial performance, environmental costs have a positive effect on financial performance, institutional ownership has a positive effect on financial performance and managerial ownership has a positive effect on financial performance